Traditional Fairy Tales and Shrek - Tchaparian, Vicky (Armenian Folia Anglistika, 2018)
Although Brothers Grimm collection of fairy tales have somehow the same cliché of plot, setting, and characters, in the fairy tale of Shrek the protagonist doesn’t follow this cliché. Shrek the protagonist is not a classical fairy tale of the handsome prince in quest of a beautiful princess; instead, he is an ogre. Grimm brothers wrote on text that they collected from the words of mouth giving the traditional tales a special structure and characters. However, compared to Grimm Brothers’ tales, Shrek the film, has a completely different structure and characters.In this paper I try to disclose the fact that Grimm folk tales which reveal the mentality of the 19th century as well as that of the earlier ages that belong to specific cultures (especially to the European culture and their mentality) are completely different than that of Shrek the film.
Keywords: Shrek; Brothers Grimm; traditional; protagonist; folk tales; animation